Using magnetic panels to enlarge a transtibial prosthetic socket. (December 2022) - Coburn, Kendrick A; DeGrasse, Nicholas S; Allyn, Katheryn J; Larsen, Brian G; Garbini, Joseph L; Sanders, Joan E
Highlights: A novel magnetic panel pull mechanism for adjustable prosthetic sockets was created. No skin irritation or discomfort was induced during amputee participant testing. Magnetic panel pull induced a 5.3% to 13.8% maximum increase in socket volume. The system may facilitate limb fluid volume recovery in prosthesis users. Abstract: A novel method is described to connect a prosthetic liner to the panels of an adjustable socket to facilitate limb fluid volume stabilization in prosthesis users. Magnets are placed in the socket panels, and iron powder is embedded in the user's prosthetic liner. When the magnet is in close proximity to the liner, a firm connection is formed. The system's capability to execute panel pull on transtibial prosthesis users was tested. The backs of the panels were supported by a bracket mounted to the external surface of the socket that allowed the radial position of the panels to be adjusted. Bench testing demonstrated an optimized strength-to-weight ratio using 1.27-cm thick annular-shaped magnets supported by 0.32-cm thick backplates. Testing on four people with transtibial amputation showed that the maximum socket increase achieved using magnetic panel pull ranged from 5.3% to 13.8% of the initial (panels flush) socket volume. The results indicate that magnetic panel pull induces a meaningful increase in socket volume during sitting. The clinical relevance is a novel strategy that may help stabilize prosthesis users' limb fluid volume over the day.